2004
DOI: 10.1111/j.1467-9450.2004.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an indoor plant on creative task performance and mood

Abstract: In this study, we investigated the effect of an indoor plant on task performance and on mood. Three room arrangements were used as independent variables: a room with (1) a plant, or (2) a magazine rack with magazines placed in front of the participants, or (3) a room with neither of these objects. Undergraduate students (M= 35, F= 55) performed a task of associating up to 30 words with each of 20 specified words in a room with one of the three room arrangements. Task performance scores showed that female parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
115
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 38 publications
(49 reference statements)
12
115
0
6
Order By: Relevance
“…Individual factors such as age, gender (Laike 1997;Reese et al 2005;Lehnung et al 2003), and disabilities (Faber Taylor et al 2002), especially concerning children, also have an impact on behaviour. Shibata and Suzuki (2004) found that indoor plants have positive effects on emotional state and creative task performance. Other studies have shown the impact of a view through a window, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Individual factors such as age, gender (Laike 1997;Reese et al 2005;Lehnung et al 2003), and disabilities (Faber Taylor et al 2002), especially concerning children, also have an impact on behaviour. Shibata and Suzuki (2004) found that indoor plants have positive effects on emotional state and creative task performance. Other studies have shown the impact of a view through a window, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as suggested by Larsen et al (1998), the existence of indoor plants increase the attractiveness and comfort of office environments. In the same vein, Shibata and Suzuki (2004) indicated the positive role of using plants on employees' creativity.…”
Section: The Role Of Work Environment Design On Individual Attitude Amentioning
confidence: 91%
“…Previous studies from different perspectives have shown that the perceived quality of the physical work environment influence people creativity (see for example: McCoy and Evans, 2002;Vithayathawornwong et al, 2003;Vischer, 2007;Oksanen and Ståhle, 2013). In fact, previous studies indicated the direct or indirect role of certain features of the physical work environment on creativity via mood (Hedge, 1982;Larsen et al, 1998;Shibata and Suzuki, 2004). For instance, Larsen et al (1998) indicated that using plants in office design can improve people's positive moods; Shibata and Suzuki (2004) specified that using plants at work can enhance people's positive mood and creativity as well.…”
Section: The Role Of Physical Work Environment On Individual and Orgamentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating nature in interior design can play an important role in creating an environment that promotes physical and mental health of the occupants (Shibata 2001(Shibata , 2004Yannick et al, 2009).…”
Section: Introductionmentioning
confidence: 99%